2015
DOI: 10.14687/ijhs.v12i1.3120
|View full text |Cite
|
Sign up to set email alerts
|

An examination of secondary school students' levels of reader self-perception ın terms of gender, grade, reading environment and frequency<p>Ortaokul öğrencilerinin okur öz algı düzeylerinin cinsiyet, sınıf, okuma ortamı ve sıklığı açısından incelenmesi

Abstract: This study aims to investigate secondary schools students' reader self-perception and its relationship with the variables gender, grade level, student's and family's reading frequency and their preferences of reading environment. In the 2013-2014 academic year, a total of 549 students including the fifth, sixth seventh and eighth grade students were randomly selected from five schools in two different cities, located in the Central Anatolia region in this study. The scores of female students' levels of reader … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Ünal (2012) analysed the effect of sixth grade students' reading attitudes upon reading comprehension and the researcher found that students' reading self-effiacy level is not at sufficient level. Baştuğ & Çelik (2015) found that secondary education students' reader self-perceptions aren't at good level. In that research, it was found that, students' 'progress' scores are at over middle level, 'observational comparison' scores are at middle level, 'social feedback' and 'physiological states' scores are at low level.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Ünal (2012) analysed the effect of sixth grade students' reading attitudes upon reading comprehension and the researcher found that students' reading self-effiacy level is not at sufficient level. Baştuğ & Çelik (2015) found that secondary education students' reader self-perceptions aren't at good level. In that research, it was found that, students' 'progress' scores are at over middle level, 'observational comparison' scores are at middle level, 'social feedback' and 'physiological states' scores are at low level.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 98%
“…Also, level of reading attitude and reading test scores are higher than boys'. Baştuğ & Çelik (2015), İnnalı & Aydın (2014) and Uçgun (2014) found that reader self-perception level varies by gender in favor of girls. Ünal (2012) found that reading attitude scores of girls are higher than boys' and girls' spend more time to reading than boys.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For those who desire to be knowledgeable and cultured, to constantly renew themselves, to think correctly, to write and speak correctly and beautifully by learning how to achieve a clear and effective way of expressing oneself, to improve themselves, and establish healthy relationships with the society (Kızgın & Baştuğ, 2020) as well as to increase their academic success in other disciplines, reading is an indispensable ability (Karatay, 2011). For that reason, the foundations of teaching how to read should be laid solid in primary school and relevant studies should be conducted on how to better enable students to gain the reading skill (Baştuğ & Çelik, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…İngiltere'deki kız öğrencilerin okur öz algıları erkek öğrencilerden daha yüksektir. İlgili alanyazında cinsiyet değişkeninin okur öz algısı üzerinde etkili bulunduğu ve kız öğrencilerin okur öz algılarının erkek öğrencilerden daha yüksek olduğunu gösteren araştırma sonuçları mevcuttur(Balcı, Uyar ve Büyükikiz, 2012;Baştuğ ve Çelik, 2015;İnnalı ve Aydın, 2014;Uçgun, 2014;Yaylı ve Duru, 2008). Cinsiyet değişkeninin okuma becerisi üzerinde bir farklılığa neden olup olmadığını belirlemek amacıylaArslan (2013) tarafından yapılan araştırmada genel olarak kızlar lehine anlamlı farklılığa ulaşıldığı ancak araştırmalarda bu farklılığın nedenlerinin tam olarak ortaya çıkarılamadığı belirtilmektedir.…”
unclassified